Improvement in liver histology due to lifestyle modification is independently associated with improved kidney function in patients with non‐alcoholic steatohepatitis. Issue 2 (16th November 2016) - Vilar‐Gomez, E.; Calzadilla‐Bertot, L.; Friedman, S. L.; Gra‐Oramas, B.; Gonzalez‐Fabian, L.; Villa‐Jimenez, O.; Lazo‐del Vallin, S.; Diago, M.; Adams, L. A.; Romero‐Gomez, M.; Chalasani, N.
Summary: Background: Several recent studies have shown a strong association between non‐alcoholic steatohepatitis (NASH) and chronic kidney disease. Aim: To examine the relationship between changes in liver histology and renal function in patients with NASH. Methods: The present analysis represents a post hoc analysis of a recently published trial that included 261 patients with NASH who were treated with lifestyle modifications during 52 weeks. Kidney function was evaluated through Chronic Kidney Disease Epidemiology Collaboration estimated glomerular filtration rates (eGFR, mL/min/1.73 m 2 ) overtime. We explored correlations between the kidney function and improvement in histological outcomes at 52 weeks. Results: Interestingly, a one‐stage reduction in fibrosis ( r = 0.20, P < 0.01) and resolution of NASH ( r = 0.17, P < 0.01) were significantly correlated with an improvement in the kidney function. The eGFR values significantly increased in patients with fibrosis improvement (+7.6 ± 6.5 mL/min/1.73 m 2 ), compared to those without fibrosis improvement (−1.98 ± 6.4 mL/min/1.73 m 2 ) ( P < 0.01) at end of treatment (EOT). Likewise, NASH resolution was associated with an increase in eGFR compared with patients without NASH resolution (2.32 ± 7.8 mL/min/1.73 m 2 vs. −1.04 ± 5.9 mL/min/1.73 m 2, P = 0.04) at EOT. After controlling for the confounders, the association between fibrosis improvement, NASH resolution and eGFR change remained significant ( P < 0.05 for both). Conclusions: Improvement in liver histology due to lifestyle modification is independently associated with improved kidney function in NASH. As new drugs for NASH emerge, studies should address whether improvement in histology in response to pharmacotherapies yield the same improvement in kidney function as weight loss. Abstract : Linked Content This article is linked to Vilar‐Gomez and Chalasani, and Gifford and Dhaun papers. To view this article visit https://doi.org/10.1111/apt.14915 and https://doi.org/10.1111/apt.13901 .